Complexity of Infection and Genetic Diversity in Cambodian Plasmodium vivax. - Lindsey R Friedrich; Jean Popovici; Saorin Kim; Lek Dysoley; Peter A Zimmerman; Didier Menard; David Serre (PLoS Neglected Tropical Diseases, 2016)
BACKGROUND:Plasmodium vivax is the most widely distributed human malaria parasite with 2.9 billion people living in endemic areas. Despite intensive malaria control efforts, the proportion of cases attributed to P. vivax is increasing in many countries. Genetic analyses of the parasite population and its dynamics could provide an assessment of the efficacy of control efforts, but, unfortunately, these studies are limited in P. vivax by the lack of informative markers and high-throughput genotyping methods. METHODOLOGY/PRINCIPAL FINDINGS:We developed a sequencing-based assay to simultaneously genotype more than 100 SNPs and applied this approach to ~500 P. vivax-infected individuals recruited across nine locations in Cambodia between 2004 and 2013. Our analyses showed that the vast majority of infections are polyclonal (92%) and that P. vivax displays high genetic diversity in Cambodia without apparent geographic stratification. Interestingly, our analyses also revealed that the proportion of monoclonal infections significantly increased between 2004 and 2013, possibly suggesting that malaria control strategies in Cambodia may be successfully affecting the parasite population. CONCLUSIONS/SIGNIFICANCE:Our findings demonstrate that this high-throughput genotyping assay is efficient in characterizing P. vivax diversity and can provide valuable insights to assess the efficacy of malaria elimination programs or to monitor the spread of specific parasites.